A C60/TiOx bilayer for conformal growth of perovskite films for UV stable perovskite solar cells. Issue 18 (12th April 2019) - Liu, Cheng; Cai, Molang; Yang, Yi; Arain, Zulqarnain; Ding, Yong; Shi, Xiaoqiang; Shi, Pengju; Ma, Shuang; Hayat, Tasawar; Alsaedi, Ahmed; Wu, Jihuai; Dai, Songyuan; et al.
Abstract : A low-temperature-processed C60 /ultrathin-TiO2 bilayer is successfully designed as an ETL for high-performance and UV-stable perovskite solar cells (1 cm 2 ). Abstract : Perovskite solar cells (PSCs) have been widely studied and such research resulted in high power conversion efficiency (PCE). However, stability remains a great challenge when TiO2 or other wide bandgap n-type oxide semiconductors are used as the electron transport layer (ETL). The use of carbon such as fullerene (C60 ) as an ETL has shown promise with much improved UV stability. But there are two major obstacles to overcome: the first is the difficulty to fabricate C60 films with full coverage mainly due to the low solubility of fullerene in dichlorobenzene and the second is the hydrophobicity of C60 that hinders the deposition of pin hole free perovskite films with high crystallinity, intimate contact, and a desired columnar microstructure. In this work, a C60 /ultrathin-TiO x (u-TiO x ) bilayer is designed and fabricated as a compact ETL, which restrains the charge recombination at the ETL/perovskite interface and significantly enhances the PSC UV stability. Not only does the introduction of TiO x on top of the C60 film fill the holes or gaps in the C60 film, but also it enhances the surface energy benefiting the growth of perovskite with an intimate contact between the ETL and perovskite, which results in an enhanced perovskite crystallization and a reduced charge recombination at the interface. Both the open-circuit voltage and fill factor were largely improved to obtain a PCE of 19.38% with a rigid device. The highest efficiency 14.74% of a larger-area flexible PSC (1.0 cm 2 ) based on the bilayer was obtained due to the superior homogeneity of the films. More importantly, by eliminating the negative charge accumulation at the perovskite/ETL interface and suppressing the irreversible moisture-driven decomposition of perovskite materials, the C60 /u-TiO x bilayer-based PSC shows outstanding stability, retaining 83% and 90% of its initial performance after 312 h UV irradiation and 1000 h exposure to ambient air, respectively.